Safety and efficacy of prophylactic treatment for hyperthyroidism induced by iodinated contrast media in a high-risk population - Manso, Jacopo; Piva, Ilaria; Censi, Simona; Clausi, Cristina; Bardi, Maria; Schiavon, Benedetta; Merante Boschin, Isabella; Tona, Francesco; Mian, Caterina (Frontiers in Endocrinology, 2023)
Introduction. The use of iodinated contrast media (ICM) can lead to thyrotoxicosis, especially in patients with risk factors, such as Graves’ disease, multinodular goiter, older age, and iodine deficiency. Although hyperthyroidism may have clinically relevant effects, whether high-risk patients should receive prophylactic treatment before they are administered ICM is still debated. Aim of the study. We aimed to demonstrate the safety and efficacy of prophylactic treatment with sodium perchlorate and/or methimazole to prevent ICM-induced hyperthyroidism (ICMIH) in a population of high-risk cardiac patients. We ran a cost analysis to ascertain the most cost-effective prophylactic treatment protocol. We also aimed to identify possible risk factors for the onset of ICMIH. Materials and Methods. We performed a longitudinal retrospective study on 61 patients admitted to a tertiary-level cardiology unit for diagnostic and/or therapeutic ICM-procedures. We included patients with available records of thyroid function tests performed before and after ICM were administered, who were at high risk of developing ICMIH. Patients were given one of two different prophylactic treatments (methimazole alone or both methimazole and sodium perchlorate) or no prophylactic treatment. The difference between their thyroid function at the baseline and 11-30 days after the ICM-related procedure was considered. Results. Twenty-three (38%) of the 61 patients were given a prophylactic treatment. Thyroid function deteriorated after the administration of ICM in 9/61 patients (15%). These cases were associated with higher plasma creatinine levels at admission, higher baseline TSH levels, lower baseline FT4 levels, and no use of prophylactic treatment. The type of prophylaxis provided did not influence any onset of ICMIH. A cost-benefit analysis showed that prophylactic treatment with methimazole alone was less costly per person than the combination protocol. On multivariate analysis, only the use of a prophylactic treatment was independently associated with a reduction in the risk of ICMIH. Patients not given any prophylactic treatment had a nearly five-fold higher relative risk of developing ICMIH. Conclusion. Prophylactic treatment can prevent the onset of ICMIH in high-risk populations administered ICM. Prophylaxis is safe and effective in this setting, especially in cardiopathic patients. Prophylaxis with methimazole alone seems to be the most cost-effective option.